After the Theological Turn: Towards a Credible Theological Grammar - Kočí, Martin (Open theology, 2022)
The theological turn provokes much debate on the nature of phenomenology but almost none on the definition of theology. I argue, however, that the theological turn not only enlarges the field of phenomenological exploration but also provides theology with a conceptual apparatus that can contribute to formulating rigorous theological positions. In the first step, I question the debate dominated by philosophers of religion which created a normative - restrictive - category of the theological turn. Instead, I argue that the full potential of the theological turn in phenomenology will only be revealed when we accept it as a descriptive category - a tendency that has always in fact been present in phenomenology. In the second step, I move towards theology to argue that the phenomenological engagements with the original theological thoughts are less de-theologized than they are transformed and in their new version offered back to theology, for which they can have crucial relevance. Hence, what is truly interesting after the theological turn is not so much the boundary between theology and phenomenology but their mutual and undeniable encounters.